Varied Clinical Presentations of Aggressive Angiomyxoma of the Vulva: A Rare Entity - Lajya Devi Goyal; Priyanka Garg; Suresh Goyal; Surabhi Bansal; Manjit Kaur Rana (Tehran University of Medical Sciences, 2024)
Objective: Aggressive Angiomyxoma (AA) of the vulva is a slow-growing mesenchymal tumour with a tendency to local invasion and recurrence. Case report: We report two cases of vulvoperineal masses that were diagnosed to be Aggressive Angiomyxomas after surgical excision. Both patients presented to the Gynaecology OPD of All India Institute of Medical Sciences, Bathinda, Punjab, India, in 2020 and 2022 with complaints of a mass coming out of introitus of three years duration and 14 years duration, respectively. The first patient was managed by surgical excision of the mass via abdominoperineal approach, while the second patient underwent vaginal hysterectomy along with the removal of the mass. Both patients were given GnRH analogues after the surgery to avoid any further recurrences and have been in remission on follow-ups so far. Conclusion: Due to its rare occurrence, clinicians should consider the possibility of AA while encountering patients with vulvovaginal masses to avoid misdiagnosis and delayed management.